(untitled) (Eurasian Journal of Philology Science and Education, 2019)
This article describes the terminology of Kazakh linguistics and its cognitive foundations. The term «linguistic terminology» is the result of the cognitive process of cognitive thinking. One of the distinguishing features of some terms is that they can be used in another discourse as a unit of speech. This problem must be addressed from the cognitive-cognitive aspect. The use of cognitive methods in the study of linguistic terms in the Kazakh language makes it possible to determine national peculiarities of linguistic phenomena, ways of developing national self-awareness in the development of scientific national terminology, and the national mentality of a linguistic personality. In this regard, as we have already said, the linguistic, cognitive bases prove that the lexical-semantic approach in the development of scientific terms is important